2016
DOI: 10.1177/0741932516637198
|View full text |Cite
|
Sign up to set email alerts
|

A Replication by Any Other Name

Abstract: Replication research is essential to scientific knowledge. Reviews of replication studies often electronically search for replicat* as a textword, which does not identify studies that replicate previous research but do not self-identify as such. We examined whether the 83 intervention studies published in six non-categorical research journals in special education in 2013 and 2014 might be considered replications regardless of using the term replicat* by applying criteria related to (a) the stated purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 60 publications
3
57
1
Order By: Relevance
“…There is growing evidence that prolonged coaching supplemented with some forms of technology-based training can play a role in Table 3. Comparison of Findings of the Current Study With Cook, Collins, Cook, and Cook (2016).…”
Section: Current Trends In Intervention Research Published In Early Cmentioning
confidence: 81%
See 1 more Smart Citation
“…There is growing evidence that prolonged coaching supplemented with some forms of technology-based training can play a role in Table 3. Comparison of Findings of the Current Study With Cook, Collins, Cook, and Cook (2016).…”
Section: Current Trends In Intervention Research Published In Early Cmentioning
confidence: 81%
“…Current study Cook et al (2016) Number helping improve practices in inclusive environments. Simultaneously, there has been an identified need in the field of ECSE for more "rigorous experimental examination of EC PD [early childhood professional development] in recent years" (Snyder, Hemmeter, & McLaughlin, 2011, p. 364).…”
Section: Criteria/itemmentioning
confidence: 99%
“…However, the findings related to replication research, for example, are inconsistent with reports that only 0.1% of journal articles in education journals are replications studies (Makel & Plucker, 2014). This discrepancy may be due to sampling bias, socially desirable responding, or education researchers engaging in research that is replicative but not explicitly identified as a replication (see Cook, Collins, Cook, & Cook, 2016). Across all Open Practices, participating education researchers self-reported a higher level of engagement than they expected from others in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Replication is considered to be at the heart of scientific inquiry (Schmidt, 2009) and critical to the scientific process because it attempts to demonstrate that the same findings can be obtained at another time, in a different place by other researchers, and as such, the results can be separated from the specific circumstances of the initial study, thus increasing the strength of the evidence of the effectiveness of the intervention (Cook, Collins, Cook, & Cook, 2016). Furthermore, replication is a means of controlling for threats to both internal and external validity that are inherent in any single study by allowing for a systematic examination of the impact of those threats across studies (Hosp, Ford, Huddle, & Hensley, 2018).…”
Section: Replicationmentioning
confidence: 99%